Espacialidades reais e fantásticas nas narrativas de Lygia Bojunga: uma leitura de A bolsa amarela, A casa da madrinha e o Sofá estampado - Maciel, Lilian Lima (2014)
This study, which focuses the literary narratives The yellow bag, The godmother\'s house and The chintz sofa, written by Lygia Bojunga, is intended to demonstrate how this author operates the linkage between the real and the imaginary, breaking the boundaries delimited by reason through objects/spaces (the bag, the house and the sofa/hole) that trigger the unusual in these narratives that constitute our corpus. It is observed in Lygia a great creativity for confabulation with the creation of a reverse world that provides children with an escape from the repression of adults; we perceive how the objects/spaces the bag, the house and the couch/hole arise as borders that open countless possibilities for characters to move between the real and unreal to develop their sorrows and anxieties, leading them to a deeper and more elaborate reading of the world and their own existence. To do so, the theoretical foundation on spatiality will be held from the theories of Michel Foucault, Gilles Deleuze and Félix Guattari. In the basis of our reflections regarding the Fantastic Literature we use Tzvetan Todorov studies, Remo Ceserani, Filipe Furtado, Freud, Louis Vax, and others; and in the grounding of the relationship between the real, the fictional and the imaginary, Wolfgang Iser s studies are addressed.